Community Perception of Tourism Planning Impact: A Case Study of Bandung Indonesia - Ahmad Candra; Nesya Amellita; Wiwik Dwi Pratiwi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The development of tourism in Bandung City is inseparable from meticulous tourism planning. However, the extent to which such planning impacts the quality of life of local residents remains a question. This study aims to fill this gap by conducting an in-depth examination of Bandung citizens' perceptions of the impacts of tourism planning on their quality of life, considering the environmental, socio-cultural, economic, and overall quality of life dimensions. Google Forms were employed as the data collection instrument. The online distribution of questionnaires enabled broader participation from various segments of the population. Data obtained from Google Forms were processed and statistically analyzed using IBM SPSS Statistics 27 to determine the extent to which the research dimensions, such as environmental impacts, socio-cultural impacts, economic impacts, and overall quality of life, are influenced by tourism planning in Bandung City. The analysis results indicate that Bandung's tourism planning has significantly contributed to improving the quality of life and economic conditions for a portion of the population. Nevertheless, there is a need for improvements in environmental management, socio-cultural aspects, and the equitable distribution of economic benefits. A more comprehensive and sustainable planning approach is required to optimize the positive impacts and mitigate the negative consequences of tourism.